2020
DOI: 10.1111/bjh.17034
|View full text |Cite
|
Sign up to set email alerts
|

Increased CD95 (Fas) and PD‐1 expression in peripheral blood T lymphocytes in COVID‐19 patients

Abstract: A low count of CD4 + and CD8 + lymphocytes is a hallmark laboratory finding in the coronavirus disease 2019 (COVID-19). Using flow cytometry, we observed significantly higher CD95 (Fas) and PD-1 expression on both CD4 + T and CD8 + T cells in 42 COVID-19 patients when compared to controls. Higher CD95 expression in CD4 + cells correlated with lower CD4 + counts. A higher expression of CD95 in CD4 + and CD8 + lymphocytes correlated with a lower percentage of naive events. Our results might suggest a shift to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 15 publications
9
75
0
Order By: Relevance
“…To this end, we observed increased CD25 + T cells in COVID-19 patients, indicating a higher state of activation (Figure 2), but also an increase in CD95 + with disease progression. This phenotype was significantly marked in severe patients, consistent with a recent study 38 . FAS has a crucial role in mediating cell death via FAS ligand engagement, as in activation-induced cell death (AICD), or by shifting cells to a more apoptotic-prone phenotype.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To this end, we observed increased CD25 + T cells in COVID-19 patients, indicating a higher state of activation (Figure 2), but also an increase in CD95 + with disease progression. This phenotype was significantly marked in severe patients, consistent with a recent study 38 . FAS has a crucial role in mediating cell death via FAS ligand engagement, as in activation-induced cell death (AICD), or by shifting cells to a more apoptotic-prone phenotype.…”
Section: Discussionsupporting
confidence: 92%
“…While previous studies have focused on lymphocyte populations 12,14,15,38 , to our knowledge the role of innate immune cells is less understood 39 . Our study highlights the expansion of MDSCs, especially G-MDSCs, in severe COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…T-cell numbers are regulated by proliferation and apoptosis during homeostasis [ 13 ], and accordingly, T-cell reduction in COVID-19 can be due to either or both of increased apoptosis and reduced proliferation rates. While Fas expression is increased in T-cells from COVID-19 [ 14 ], T-cell data in Zhu et al showed that Fas, FasL, and Caspase-3 [ 15 ], which play key roles of T-cell apoptosis, were not significantly increased in COVID-19 patients [ 16 ]. Interleukin (IL)-7 is a key cytokine for T-cell homeostasis, sustaining the naïve T-cell pool [ 17 ].…”
Section: Textmentioning
confidence: 99%
“…This was accompanied by an increased expression of PD-1 molecules and apoptotic marker, CD95, on T cells and was ascertained regardless of age. The PD-1 levels were positively correlated with CD95 on T cells, indicating the bias of T cells towards exhaustion and apoptosis [152]. This clearly shows that the SARS-CoV-2 virus is intensifying PD-1 protein expression on T cells and driving them to a state of exhaustion and hampering the protective T cell immunity, especially among those who are in a critical condition requiring intensive care unit (ICU) support.…”
Section: Pd-1/pd-l1 Axis During Acute Infections In Blood Vessel Inflmentioning
confidence: 94%